Trends and Inpatient Outcomes of Venous Thromboembolism-Related Admissions in Patients with Philadelphia-Negative Myeloproliferative Neoplasms - Katiyar, Vatsala; Uprety, Alok; Mendez-Hernandez, Andres; Fuentes, Harry E.; Andrade, Xavier A.; Zia, Maryam (TH Open, 2019)
Background Patients with Philadelphia-negative myeloproliferative neoplasms (MPNs), including polycythemia vera (PV), essential thrombocytosis (ET), and primary myelofibrosis (MF), have a significant risk of venous thromboembolism (VTE). We aim to determine the trends in annual rates of VTE-related admissions, associated cost, length of stay (LOS), and in-hospital mortality in patients with MPN.Methods We identified patients with PV, ET, and MF from the Nationwide Inpatient Sample (NIS) database from 2006 to 2014 using ICD-9CM coding. Hospitalizations where VTE was among the top-three diagnoses were considered VTE-related. We compared in-hospital outcomes between VTE and non-VTE hospitalizations using chi-square and Mann–Whitney U-test and used linear regression for trend analysis.Results We identified 1,046,666 admissions with a diagnosis of MPN. Patients were predominantly white (65.6%), females (52.7%), with a median age of 66 years (range: 18–108). The predominant MPN was ET (54%). There was no difference in in-hospital mortality between groups (VTE: 3.4% vs. non-VTE: 3.2%; p = 0.12); however, VTE admissions had a longer LOS (median: 6 vs. 5 days; p < 0.01) and higher cost (median: VTE US$32,239 vs. 28,403; p ≤ 0.01).The annual rate of VTE admissions decreased over time (2006: 3.94% vs. 2014: 2.43%; p ≤ 0.01), compared with non-VTE–related admissions.Conclusion In our study, VTE-related admissions had similar in-hospital mortality as compared with non-VTE–related admissions. The rates of hospitalizations due to VTE have decreased over time but are associated with a higher cost and LOS. Newer risk assessment tools may assist in preventing VTE in high-risk patients and optimizing resource utilization.
Keywords: venous thromboembolism; myeloproliferative neoplasm; polycythemia vera; essential thrombocytosis; primary myelofibrosis